Design and Performance Characterization of the E-Core Outer-Rotor Hybrid-Excitation Flux Switching Machine - Zhiyuan Xu; Ming Cheng (Energies)
This paper proposes an E-core outer-rotor hybrid-excitation flux switching (OR-HEFS) machine for in-wheel direct driving application. According to the general air gap field modulation theory, the magneto-motive force (MMF) permeance model was established to investigate the air gap flux density, and then the torque generation, the flux regulation principle, and the excitation-winding-induced voltage of the E-core OR-HEFS machine were analyzed. To characterize the output performances, the influence of the design parameters was investigated for the E-core OR-HEFS machine, including the split ratio, stator tooth arc, PM arc, fault-tolerant tooth arc, rotor tooth arc, stator yoke width and rotor yoke width. The performances contained the output torque, torque ripple, flux regulation ratio, and the excitation-winding-induced voltage. On this basis, the aforementioned four performances were optimized by means of the non-dominated sorting genetic algorithm II (NSGA-II). Based on the optimization result, a prototype was manufactured and tested to verify the whole investigation of this paper.